The History of Miss Jane Pittman - Christopher Mulvey (Transatlantica)
This paper explores the ways in which Ernest J. Gaines uses fiction in The Autobiography of Miss Jane Pittman to write a history of the African American from 1861 to 1961. The “Introduction” sets the novel going, but its direction has already been given in the unusual dedication to his grandmother, stepfather and aunt “who did not walk a day in her life but who taught me the importance of standing” (Gaines iv). The significance for Gaines is that what happened a hundred years ago is part of his present-day lived life.The nineteenth-century novel was possessed by history, and white nineteenth-century novelists found their great subject in the war of European nations that was fought between 1799 and 1815. But that was not an American war nor was it an African American war. For Gaines, the war that makes the great turning point of a nation and a people is the American Civil War, fought from 1861 to 1865. It resulted in a moment of history after which life would not be the same. However, one of the main points that Gaines makes about that great turning point in history is that everything changed and nothing changed. And his main fictional device to establish that truth is to tell the history of the hundred years since Emancipation as the story of one woman. Her autobiography becomes an ethno-biography.The continuity forwards from 1861 is given through the life of one woman, but Gaines’s uses another device to provide a continuity backwards from 1861. The young man who wants to get Miss Jane Pittman’s story upsets her with his persistence: “What you want know about Miss Jane for?’ Mary said. ‘I teach history,’ I said. ‘I’m sure her life’s story can help me explain things to my students.’ ‘What’s wrong with them books you already got?’ Mary said. ‘Miss Jane is not in them,’ I said” (Gaines v). Ernest J. Gaines wrote at a time when historians finally began to recognize that they could get no true history of the South if they allowed that history to be written by plantation owners. In the sixties and the seventies, the pre-Civil War slave narratives, so long dismissed as lies and fictions by white Southern historians, began to be read again, and began to tell African Americans another history. Gaines used the then un-mined resources of the slave narratives to provide structure, themes, characters and incidents for his novel. A comparison of The Autobiography of Miss Jane Pittman with the Narrative of William W. Brown, A Fugitive Slave Written by Himself, published in 1847, will show how close these links are. But William Wells Brown’s Narrative is only one of at least sixty pre-Civil War slave narratives, and, though it is an exceptionally good one, there is another reason for singling out its author. William Wells Brown was the first African American to publish a novel: Clotel; or the president’s daughter. That appeared in 1853, and up to that date Brown, like Equiano, Douglass, Bibb, Henson, Pennington, and the many others who wrote an account of their life as a slave and their escape from the South had had to contend with the Southern cry that everything the fugitive slaves was saying was lies, and that they did not write their own stories but got white Northerners to write them for them. It was the publication of Harriet Beecher Stowe’s Uncle Tom’s Cabin in 1852 which showed William Wells Brown (and Frederick Douglass) that fiction might serve the abolitionist cause as much as a true narrative faithfully attested.In 1853, with the publication of his novel Clotel, William Wells Brown took African American narrative in a direction that was new and dangerous. In 1971, with the publication of his novel Miss Jane Pittman, Ernest J. Gaines returned African American fiction to its roots, and he did so with a didactic purpose remarkably like that of William Wells Brown. For all that he had been a slave there, Brown seems to have loved the South more than he loved the North. He called his last work My Southern Home, and he was never at home in the North. To his dismay and disgust when he reached Ohio and freedom in 1834, he found a physical hatred of blacks that he had not experienced in the slave states. He had run from Slavery to Segregation. And that is the story that Miss Jane Pittman has to tell of African Americans running from 1861 to 1961.